HUBUNGAN KADAR TIMBAL (Pb) UDARA DENGAN KADAR TIMBAL (Pb) DALAM DARAH PADA PEKERJA PENGECATAN INDUSTRI KAROSERI DI SEMARANG - Mustafiroh Kasanah; Onny Setiani; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Lead (Pb) is one of the pollutant in the air, in small quantities these particles can cause poisoned. Workers at painting section are very risky of lead exposure that contained in paint in the workplace. This study aims to determine the correlation of air lead (Pb) levels and blood lead (Pb) levels among workers in Karoseri industry Semarang. This study used observational research with cross sectional approach. The population study were workers at painting sector in Karoseri industry Semarang with sample of 34 workers. Data analysis using Rank Spearman correlation test. The measurement results showed that the mean of air lead (Pb) levels in the painting workplace section in Karoseri industry Semarang was within normal limits (0.05 mg/m3) is 0.00336 ± 0.00346 mg/m3. The mean blood lead (Pb) levels among workers has exceeded the normal limit (≤10 mg/dl) is 34.4 ± 16.7 mg/dl and 85.3% of respondents had higher blood lead (Pb) levels exceeded normal limit (≤10 mg /dl ). Statistical analysis showed no correlation between air lead (Pb) levels with blood lead (Pb) levels among workers at painting section in Karoseri industry Semarang (p value = 0.403). Suggestions for company, take measurement of the ambient air lead (Pb) levels and blood lead (Pb) levels on a regular basis, once a year. For workers are expected to use Personal Protective Equipment (PPE) in accordance with Indonesian National Standard (SNI).